Transmission Electron Microscopy and Diffractometry of Materials - Fultz, Brent 1955-; Howe, James M. 1955- (Springer Berlin Heidelberg, 2002)
This textbook develops the concepts of transmission electron microscopy (TEM) and x-ray diffractometry (XRD) that are important for the characterization of materials. It emphasizes themes common to both techniques, such as scattering from atoms, wave interference, and the formation and analysis of diffraction patterns. It explains the uniqueness of each technique, especially imaging and spectroscopy in the TEM. Simple citations of rules are avoided as much as possible, and both practical and theoretical issues are explained in detail. The book can be used as both an introductory and advanced-level graduate text since sections/chapters are sorted according to difficulty and grouped for use in quarter and semester courses on TEM and XRD. Numerous problems are provided at the end of each chapter to reinforce key concepts, and solutions are available to instructors. Appendices provide procedures for introductory laboratory exercises, and up-to-date tabulations of physical data useful for TEM and XRD.